Archaeobotanical studies of past plant cultivation in northern Europe (Advances in archaeobotany, 2020)
Plant cultivation has a long and successful history that is tightly linked to environmental and climate change, social development and to cultural traditions and diversity. This is true also for the high latitudes of northern Europe, where cultivation started thousands of years before the earliest written records. The long history of cultivation can be studied by archaeobotany, which is the study of ancient seeds, pollen and other plant remains found on archaeological sites.00This book presents recent advances in North-European archaeobotany. It focuses on plant cultivation and brings together studies from different countries and research environments, both at universities and within contract archaeology.00The studies cover the Nordic countries and adjacent parts of the Baltic countries and Russia, and they span more than 5.000 years of agricultural history, from the Neolithic to the Middle Ages. They highlight and discuss many different aspects of early agriculture, from the first introduction of cultivation, to crop choices, expansions and declines, climatic adaptation, and vegetable gardening.